2021
DOI: 10.3390/ijerph18073459
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis Prevalence, Severity, and Risk Factors: A Comparison of the AAP/CDC Case Definition and the EFP/AAP Classification

Abstract: Background: This cross-sectional study evaluated the utility of the 2018 European Federation of Periodontology/American Academy of Periodontology (EFP/AAP) classifications of epidemiological studies in terms of periodontitis severity, prevalence and associated risk factors and the 2012 American Academy of Periodontology/Centers for Disease Control and Prevention (AAP/CDC) case definitions. Methods: We included 488 participants aged 35–74 years. Measurements were recorded at six sites per tooth by two qualified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 33 publications
9
43
1
Order By: Relevance
“…However, these were not designed for research purposes and impose very low thresholds for CAL and PD, rendering its use and value in this analysis questionable. In fact, we did calculate the prevalence using this data and found that approximately 99% were found to have periodontitis, similar to findings based on another study (Germen et al, 2021; Ghassib et al, 2021; Stødle et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…However, these were not designed for research purposes and impose very low thresholds for CAL and PD, rendering its use and value in this analysis questionable. In fact, we did calculate the prevalence using this data and found that approximately 99% were found to have periodontitis, similar to findings based on another study (Germen et al, 2021; Ghassib et al, 2021; Stødle et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, no other agreement analysis between the two case definitions is currently available although other recent studies reported on periodontitis in relation to the two classification systems [64,65]. This point highlights one main strength of our study, which lies in the validity assessment of the 2018 EFP/AAP classification of periodontal conditions in a specific group of IS patients.…”
Section: Discussionmentioning
confidence: 64%
“…did not describe an appropriate diagnostic test for comparison, presenting only descriptive data on the prevalence of severe periodontitis according to the two definitions—being 16.8% (CDC/AAP) and 34% (EFP/AAP). However, it was reported that patients with PD ≥6 mm, although not presenting with clinical AL ≥5 mm, were classified as EFP/AAP Stages III and IV 33 . Therefore, these data must be observed with caution since a larger number of subjects may have been classified as severe periodontitis according to the EFP/AAP definition, which may explain why the prevalence of these cases is twice the prevalence of cases according to the CDC/AAP case definitions.…”
Section: Discussionmentioning
confidence: 96%